Relationship between transformational leadership and positive youth development in Japanese sports - Nakayama, Saori; Izawa, Makoto (Frontiers in Sports and Active Living, 2025)
IntroductionThis study examined the relationship between transformational leadership (TFL) behaviors of coaches and positive youth development (PYD) outcomes in Japanese youth sports settings. Research has shown associations between TFL and various athlete outcomes in Western sports contexts. However, limited attention has been paid to how cultural factors shape these relationships in East Asian settings, particularly within Japanese sports culture that emphasizes hierarchical relationships and collectivist values.MethodsThe study included 112 first-year undergraduate students from a sports science program at a Japanese university. Athletes' perceptions of their coaches' TFL behaviors and PYD outcomes were assessed using the Differentiated Transformational Leadership Inventory for Youth Sport (DTLI-YS) and the Youth Experience Survey for Sport (YES-S).ResultsCorrelation analyses revealed a particularly strong association between high performance expectations and initiative (r = .53, p < .01), notable when compared to American research where correlations between PYD outcomes and TFL dimensions were typically weaker (r = .11 – .43). Regression analyses further showed that high performance expectations were significantly associated with both goal setting (β = .29, p < .05) and initiative (β = .39, p < .01). Analysis by competition level revealed significant differences in initiative (F = 4.07, p < .01, η² = .10) and total YES-S scores (F = 2.75, p < .05, η² = .07).DiscussionThese findings contribute to understanding how cultural context shapes the relationship between coaching leadership and youth development in sports. While the prominence of high performance expectations reflects Japanese sports culture's emphasis on discipline and collective achievement, results suggest the importance of incorporating a more balanced leadership approach that includes elements beyond high performance expectations to foster comprehensive athlete development.